In Vitro Biomechanical Comparison of a 5‐Hole 4.5 mm Locking Compression Plate and 5‐Hole 4.5 mm Dynamic Compression Plate for Equine Proximal Interphalangeal Joint Arthrodesis. Issue 5 (11th February 2014) - Seo, Jong‐pil; Yamaga, Takashi; Tsuzuki, Nao; Yamada, Kazutaka; Haneda, Shingo; Furuoka, Hidehumi; Sasaki, Naoki
<x xml:space="preserve">Abstract</x> Objective To compare the biomechanical properties of a 5‐hole 4.5 mm narrow locking compression plate (LCP) and 5‐hole 4.5 mm narrow dynamic compression plate (DCP) for equine proximal interphalangeal (PIP) joint arthrodesis. Study Design Experimental mechanical study. Animals Cadaveric adult equine forelimbs (n = 6 pair). Methods For each forelimb pair, 1 PIP joint was stabilized with LCP and the contralateral PIP joint with DCP. The 6 construct pairs were tested using a single‐cycle, 3‐point dorsopalmar bending system. PIP joints were evaluated with pre‐ and post‐test radiography. Results The LCP technique had significantly greater yield load, failure load, and stiffness under single‐cycle, 3‐point dorsopalmar bending to failure than the DCP technique. There was no significant difference between the 2 constructs for displacement at yield and failure point. Conclusions Biomechanically, the LCP technique provided significantly greater stability than the DCP technique under the test condition.